(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The forthcoming of LED technology to produce high-quality white light with unprecedented energy productivity is the impetus for the intense level of study and improvement now. In this presentation, the effect of the red, blue light emitting diodes (LED) and white fluorescent lampson in the morphogenesis of tomato seedling grown in vitro have been studied by using four groups of light-emitting diode under four levels of the light intensity to determine the combined influence of the light in tomato. Six morphological factors record under treatments are taken in vitro. Maximum rate of the plant length, number of nodes , number of branch and number of leaves, have been obtained in (6:2:1) spectral (LED) mixture, with decreaseing of light intensity at 500 and 1000 lux. In conclusion, the contribution of red and blue light to significant affected the morphology and quality of tomato seedling in micropropagation